Determinants of the use of financial technology (Fintech) in Generation Y - PHIMOLSATHIEN, T. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The purpose of this research is to study the level of behavior of the use of financial technology (Fintech) and the factors that influence Generation Y behavior with a diploma lower or equal to high school. The results of the qualitative study found that the approaches to promote the use of technology for Generation Y financial transactions, include educating the user in order to promote the use of technology. RESUMEN El propósito de esta investigación es estudiar el nivel de comportamiento del uso de la tecnología financiera (Fintech) y los factores que inciden en la Generación Y con diploma inferior o igual a secundaria. Los resultados del estudio cualitativo encontraron que los enfoques para promover el uso de tecnología para las transacciones financieras de la Generación Y incluyen educar al usuario con el fin de promover el uso de la tecnología.